2005
DOI: 10.2334/josnusd.47.105
|View full text |Cite
|
Sign up to set email alerts
|

The effect of IL-l.ALPHA. and nifedipine of cell proliferation and DNA synthesis in cultured human gingival fibroblasts

Abstract: The effect of nifedipine and interleukin-α (IL-1α) on the cell proliferation and DNA synthesis was studied in human gingival fibroblasts derived from 5 patients who developed gingival overgrowth (nifedipine responders) and 5 patients who did not develop gingival overgrowth (nifedipine non-responders) in response to nifedipine. Epidermal growth factor was used as a positive control. The fibroblasts derived from nifedipine responders tended to have a numerically greater rate of cell proliferation and DNA synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Additionally, nifedipine more than amlodipine stimulated (cardiac) fibroblasts [32], which was undesired in that case but hopeful for wound healing. A similar stimulatory effect of nifedipine was observed in patients who had developed a gingiva hyperplasia after long-term intake [12, 33]. However, in gingiva fibroblasts the influence on the collagen matrix dominated.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Additionally, nifedipine more than amlodipine stimulated (cardiac) fibroblasts [32], which was undesired in that case but hopeful for wound healing. A similar stimulatory effect of nifedipine was observed in patients who had developed a gingiva hyperplasia after long-term intake [12, 33]. However, in gingiva fibroblasts the influence on the collagen matrix dominated.…”
Section: Discussionmentioning
confidence: 57%
“…Especially timolol exerted a pro-proliferative effect after local application [8]. Bhaskar et al [11] demonstrated that the calcium channel blocker amlodipine enhances the tensile strength of wounds, but not the epithelialization [12, 13]. In contrast to these rather beneficial effects, angiotensin-converting enzyme (ACE) blockers affected proliferation and migration of skin cells negatively [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the unique hyper-responsiveness of androgen receptor mRNA levels in response to IL-1␤ in nifedipine-induced gingival overgrowth cells may explain the link between the stimulatory effect of pro-inflammatory cytokine, elevated levels of adrenal androgen, and increased repair potential in nifedipine-induced gingival overgrowth fibroblasts. It was also shown that IL-1␣, a potent IL-1␤ analogue, exerted a synergistic effect with nifedipine on cell proliferation and DNA synthesis in cultured human gingival fibroblasts (Sato et al, 2005). We propose that this pro-inflammatory cytokine plays a major role in modulating soft-tissue enlargement in nifedipine-induced gingival overgrowth.…”
Section: Discussionmentioning
confidence: 95%
“…IL-1 has been reported to be a potential regulator of fibroblast proliferation (10 -12), with significantly higher levels found in the gingival crevicular fluid of patients with periodontal disease (13,14). We have previously shown that a mixture of nifedipine and IL-1α increased cell proliferation, suggesting that IL-1α may be a co-factor for nifedipine-induced gingival overgrowth (15,16). We have also demonstrated that IL-1α, but not nifedipine, accelerates the formation of intercellular basic fibroblast growth factor (bFGF) in cultured human gingival fibroblasts (17).…”
Section: Introductionmentioning
confidence: 99%